Kritik Terhadap Interaksi Antar Ruang DDN Pengguna di Masjid Istiqlal Jakarta - Nurul Irsyadah; Dewi Sukma Intami (Misterius : Publikasi Ilmu Seni dan Desain Komunikasi Visual., 2024)
Istiqlal Mosque, located in Jakarta, is an important symbol of Indonesian independence and the largest mosque in Southeast Asia. Designed by architect Frederich Silaban, the building combines modern architectural design with traditional Islamic elements. The mosque's main function is as a place of worship for Muslims, but it also has important social, religious and educational roles. With a capacity of more than 200,000 worshipers, the mosque is not only a place for congregational prayers, but also a center for activities such as recitation and celebrations of Islamic holidays. The mosque's spacious and open design allows for strong interaction between worshipers, creating social bonds that strengthen their spiritual connection. Apart from being a place of worship, Istiqlal Mosque also reflects a symbol of Indonesia's unity and national identity. Its location next to the Jakarta Cathedral Church illustrates the importance of interfaith tolerance in Indonesia. The mosque is also a center for da'wah and Islamic studies that invites many visitors from various backgrounds to exchange knowledge and deepen their understanding of Islam. As a religious tourism destination, the mosque attracts many tourists who want to experience peace and learn about its history and symbolism. Through its various functions, Istiqlal Mosque not only acts as a place of worship, but also as a social space that strengthens relationships between its users, reflecting the spirit of nationality and deep spirituality.